Acoustic similarity elicits responses to heterospecific distress calls in bats (Mammalia: Chiroptera). (December 2018) - Huang, Xiaobin; Metzner, Walter; Zhang, Kangkang; Wang, Yujuan; Luo, Bo; Sun, Congnan; Jiang, Tinglei; Feng, Jiang
Abstract : Frequently, individuals of one species respond to alarm calls produced by another species. This form of interspecies communication can be critical for survival. How animals recognize and respond to heterospecific alarm calls is, however, still poorly understood. This is especially true for bats, which are highly vocal and possess a specialized auditory system. We hypothesized that, among bat species, acoustic similarity between heterospecific and conspecific alarm calls is a key factor that underlies call recognition. However, this ability could also be acquired via associative learning from prior exposure or result from phylogenetic relatedness among caller and receiver species, as shown by others. Here we focused on distress calls of bats as representing a certain type of alarm call. To test our hypothesis, we recorded distress calls of 11 bat species from four families at five different sites. We broadcast the recorded calls to three of these species ( Rhinolophus sinicus, Myotis badius and Myotis laniger ). For all three species, neither prior exposure (familiarity) nor phylogenetic relatedness explained the variation in the response strength, as measured by echolocation vocalizations of receiver species in response to playback of heterospecific distress calls. In contrast, acoustic similarity, especially in peak frequency, between conspecific and heterospecific distress calls, was positively correlated with response strength in the receiver species. Thus, our findings emphasize that, at least among bats, acoustic similarity is a key factor allowing recognition of heterospecific alarm calls. It remains unclear whether evolutionary, genetic and/or neurophysiological mechanisms entrain an individual to respond selectively to a specific acoustic feature. Highlights: We investigated recognition of heterospecific distress calls in bats. The recognition of heterospecific distress calls is an unlearned behaviour. Acoustic similarity elicits responses to heterospecific distress calls. Peak frequency plays a key role in the response to heterospecific distress calls.